The Relationship of Cultural Intelligence, Student’s Innovative Work Behavior and The Influence of Interpersonal Trust: Case Study of Indonesian International Student Mobility Awards - Nur Arief Rahmatsyah Putranto; Feodora Putri Humaira (Integrasi Sains Media, 2023)
Rapidly shifting market due to globalization increases the nation's demand for young innovators. Innovators from Generation Z are needed to support the future growth of Indonesia. There are several Indonesian Government initiatives to elevate Indonesian education to grow innovations, such as establishing an international student mobility scholarship program. However, research on how the program can increase innovative work behavior for Indonesian students is still unclear. This research aims to investigate how Indonesian students perceive the impact of international student mobility on their innovative work behavior, focusing on the role of cultural intelligence and its effect on innovative work behavior through interpersonal trust. A quantitative approach was adopted for this study to examine the relationships between the variables with the assistance of SmartPLS 4.0 software. An online questionnaire was distributed to 302 respondents consisting of Indonesian students who had completed the Indonesian International Student Mobility Awards program in 2022 from all host country regions. This study demonstrates that students with higher cultural intelligence positively influence their individual innovative work behavior. Interpersonal trust also influences the process as a mediating role in the relationship between cultural intelligence and innovative work behavior among students in multicultural environments. This study can be a reference for future research and stakeholders to improve education quality by focusing on the impact of cultural intelligence on students' innovative work behavior in the context of cross-cultural interaction, specifically Indonesian students that participate in international student mobility programs from the Indonesian government. Such research has not been explored extensively beforehand, making this study valuable addition to the pedagogy and management science field.